Trading Nudes Like Hockey Cards: Exploring the Diversity of 'Revenge Porn' Cases Responded to in Law. (June 2021) - Dodge, Alexa
Popular and scholarly responses to nonconsensual pornography (colloquially known as 'revenge porn') have largely, though not exclusively, focused on cases that fit within the paradigmatic mold of men nonconsensually distributing intimate images with the intention to harass or abuse their female partners/ex-partners. However, several recent studies offer evidence that the dynamics of this act are more diverse than previously assumed. In this article I analyze 49 Canadian legal cases to determine the extent to which those cases that make it to the court level fit within the typical framing and to explore the dynamics of cases laying outside this paradigm. I find that, while a large portion of cases fit the commonly imagined pattern, the case law also includes several cases that complicate dominant framings of nonconsensual pornography. Using intersectional and postmodern feminist theory, I argue that this variety of case contexts necessitates more diverse socio-legal understandings of and responses to nonconsensual pornography.